Loss of bone mineral density and trabecular bone score in elderly hemodialysis patients: a 2-year follow-up, prospective, single-centre study - Brunerová, Ludmila; Kasalický, Petr; Verešová, Jana; Lažanská, Renata; Potočková, Jana; Rychlík, Ivan (International urology and nephrology, 2020)
BACKGROUND: Low bone mineral density (BMD) and trabecular bone score (TBS) are established risk factors for fractures even in hemodialysis population and they seem to be significantly lower in comparison with general population. The aim of our study was to describe 2-year loss of BMD and TBS and their predictors in hemodialysis patients. METHODS: From 59 non-selected patients (mean age 67.6 ± 13.1 years) from one dialysis centre, treated with hemodiafiltration (HDF), clinical and laboratory characteristics were obtained and densitometry examinations (with BMD and TBS results) were performed initially and at the end of 2-year follow-up. RESULTS: Two-year decrease in BMD of lumbar spine reached 4.1% (ns), of proximal femur 9.1% (p = 0.004), and of femoral neck 1.3% (ns). In the co-educated cohort, BMD decrease in all the sites correlated significantly with age and only the change of BMD of lumbar spine was negatively associated with serum calcium (r = - 0.39; p = 0.04) and dialysis vintage (r = - 0.387; p = 0.062), no other predictors of BMD loss were identified. Some predictors of BMD loss were identified with regard to gender. TBS decrease was 0.05 (3.9%; p = 0.03), and similarly, it was not predicted by any of selected parameters. No differences in BMD changes or TBS were observed between the patients with and without fractures. CONCLUSIONS: In patients with HDF, significant BMD and TBS annual losses were observed, and they were associated only with age and (in BMD of lumbar spine) with serum calcium and dialysis vintage.
Keywords: kostní denzita; krček femuru; Adult; senioři; Absorptiometry, Photon; Bone Density; bederní obratle; Aged; osteoporotické fraktury; Male; BMD; lidé; lidé středního věku; Humans; vápník; Femur Neck; sexuální faktory; Age Factors; Follow-up; trabekulární kostní tkáň; Middle Aged; Sex Factors; věkové faktory; Lumbar Vertebrae; Calcium; TBS; Osteoporotic Fractures; senioři nad 80 let; hemodiafiltrace; Aged, 80 and over; Osteoporosis; rizikové faktory; mužské pohlaví; osteoporóza; Hemodiafiltration; následné studie; dospělí; Loss; prospektivní studie; ženské pohlaví; chronické selhání ledvin; Cancellous Bone; Follow-Up Studies; absorpční fotometrie; Female; Kidney Failure, Chronic; Risk Factors; Hemodialysis; Prospective Studies